RISK SOCIETY, NATION STATES AND IMMIGRANTS: MEDIA AND RISKS UNDER GLOBALISATION CONDITIONS - Özkan, Devrim (International Journal of Contemporary Economics and Administrative Sciences, 2017)
This study analyses the opposition of globalisation and nationalism (and/or localism) exclusively within the scope of international migration problem. Within the first decade of the 21st century, the rapidly increasing oppositions between supranational economic and political structures have become decisive forces in society and politics. The ideals based on Enlightenment, universalistic discourses, those shaping the course of globalisation, have been confronted by nationalist political movements trying to preserve their identity. This encounter has the potential to become a major catalyst as the source of political and social problems in the 21st century. International migration has increased due to globalisation, so triggering risks and conflicts, while it has caused a strengthening of radical nationalist movements defining themselves in terms of other identities. In addition, the media, which has long been used as an ideological apparatus to create a uniform identity by the manipulations of centralised supranational, has been weakening the sovereignty of the nation state. Therefore, the controversy between economic tendency towards globalisation and the native features and interests of politics has been rapidly increasing. Within this scope, the current study analyses the social, economic and political problems caused by the risks arising from the opposition of globalisation and nationalism.